Problems associated with psychological barriers in general professional training of future doctors - Ya. T. Zhakupova; O. A. Shumakova; V. S. Chulkov; E. N. Serebryakova; V. A. Shumakov (Кардиоваскулярная терапия и профилактика)
Aim. To identify psychological barriers in general professional training of doctors, expressed in mental state changes and its relationship with mastery of the disciplines of general professional training.Material and methods. A total of 189 student volunteers from the South Ural State Medical University aged 18 to 22 years (men 58; women, 131) participated in the study. The experimental groups (EG) consisted of the first (EG-1), third (EG-2), and sixth (EG-3) year pediatric students. To study the mental state of students, the following psychodiagnostic methods were used: the Beck Depression Inventory, the SpielbergerHanin anxiety test, Heck and Hess rapid neurosis diagnosis. The determination of individual characterological features was carried out using the character accentuation method by G. Schmishek. Statistical analysis was carried out using the Mann-Whitney U-test, correlation analysis (Spearman rank correlation coefficient).Results. During the study at a medical university, students experience changes in their individual and personal mental characteristics, which are qualitatively transformed into psychological barriers to general professional training and mastery of general professional competencies. The most "dangerous" indicator, influencing both personal well-being (mental health) and the success of general professional training of future doctors, is the predisposition of students to neurotic disorders. It increases towards the end of study at the university, which is associated with the increasing level of difficulty of the educational material, the crisis of self-identification, and problems in forming a professional orientation of a personality, and personally significant issues in employment and admission to residency.Conclusion. There are following means of psychoprophylaxis of stress and neurotic disorders in students of medical universities: early diagnostics of neurotic disorders, psychological training on human mental health, destructive pathologies; motivation aimed at overcoming neurotic forms of response, in conditions of cooperation and mutual understanding between teachers and students; formation of mental selfregulation skills, development of a sense of humor through educational work.